2018
DOI: 10.1007/s00792-018-1040-9
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and diversity of prokaryotes in ephemeral hypersaline lake Chott El Jerid using Illumina Miseq sequencing, DGGE and qPCR assays

Abstract: Chott El Jerid is the largest hypersaline ephemeral lake in southern Tunisian Sahara desert and is one of the biggest depressions at the North of Africa. This study aimed to investigate the diversity and abundance of microbial communities inhabiting Chott El Jerid during wet season (when it was flooded), using molecular methods [Illumina Miseq sequencing, DGGE and qPCR (qPCR)]. 16S rRNA gene analyses revealed that bacterial community was dominated by Proteobacteria (especially Ralstonia species), followed by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 47 publications
6
18
0
Order By: Relevance
“…Predominant DGGE bands were excised, reamplifed, and sequenced. Sequences and phylogenetic analysis of the rRNA 16S sequences were performed as previously reported (BenAbdallah et al, 2018).…”
Section: Pcr-dgge and Sequence Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Predominant DGGE bands were excised, reamplifed, and sequenced. Sequences and phylogenetic analysis of the rRNA 16S sequences were performed as previously reported (BenAbdallah et al, 2018).…”
Section: Pcr-dgge and Sequence Analysismentioning
confidence: 99%
“…Sequencing of PCR amplicons of 16S rDNA was conducted with the Illumina MiSeq platform (CBS, Sfax, Tunisia) targeting the V3-V4 hypervariable regions using prokaryotic universal (Pro341/Pro805R) primer sets (Takahashi et al, 2014) for 2 × 300 bp paired-end sequencing (Illumina). The amplification of PCR products and Illumina library preparations were achieved as previously reported (BenAbdallah et al, 2018). Raw data acquired from the Illumina MiSeq sequencing platform were analyzed using the QIIME software package 1.9.1 (Caporaso et al, 2010) as previously described (BenAbdallah et al, 2018).…”
Section: Illumina Sequencing and Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Halophiles thrive in hypersaline niches and have potential applications in biotechnology [1,2]. Microbial diversity in most hypersaline environments is often studied using culture-dependent and -independent methods [3][4][5][6][7]. Previous studies have shown that the taxonomic diversity of microbial populations in terrestrial saline and hypersaline environments is relatively low [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for lakes with strong dynamics within a month, this uncertainty increases. respectively, strong differences between two datasets correspond to months with rapid water changes in response to erratic rainfall events (Ben Abdallah et al 2018;Bryant 1999). These examples demonstrate that a low to moderate correlation between both datasets does not necessarily imply a poor accuracy of MODIS SWF, but rather that MODIS allows to capture rapid temporal changes.…”
Section: Sources Of Error Andmentioning
confidence: 99%